A Rare Co-Occurrence of Triple Mutations in JAK2, CALR, and MPL in the Same Patient with Myelofibrosis - Sherine J. Thomas; D. P. Dash (Case Reports in Hematology)
Background. The diagnosis and prognostication of myeloproliferative neoplasm rely on the presence of driver mutations in JAK2, calreticulin (CALR), and MPL mutations. In the past, the presence of these mutations was thought to be mutually exclusive. Since then, there have been multiple reports of the presence of dual mutations. The presence of all three driver mutations in the same patient with myelofibrosis has not been previously described. Case. A 73-year-old female underwent a hematological workup in our facility after a routine hemogram performed prior to complex ophthalmological surgery revealed severe thrombocytosis. A comprehensive workup including an NGS panel for MPN driver mutations demonstrated that she had a calreticulin type-1 mutation, a JAK2 exon 14 (JAK2L611S) mutation, and an abnormal hotspot variant for MPL with VAF1%. A bone marrow biopsy confirmed a myeloproliferative neoplasm with grade 2 reticulin fibrosis suggesting primary myelofibrosis. Molecular profiling of bone marrow confirmed the previously noted mutations and an MPLW515R mutation. The patient was started on treatment with hydroxyurea and aspirin with improvement in platelet count and resolution of anemia. Discussion. The clinical significance of the presence of multiple driver mutations in the same patient is not well understood at this time. There have been 11 publications between 2014 and 2020 that have described dual mutations of JAK2V617F, MPL, and CALR mutations. The JAK2 exon 14 mutation noted, in this case, is JAK2L611S which has not previously been reported in MPN and only reported in 5 cases in the COSMIC database. The JAK2 exon 14 mutation identified in this case is not an established driver mutation for myeloproliferative neoplasm, and its clinical implication remains unknown. Conclusions. The above case in addition to recent case reports and case series supports the use of broader NGS sequencing panels for diagnosis and prognostication of MPN. These mutations should not be considered mutually exclusive. The clinical behavior and prognosis of the subgroup with multiple mutations need to be studied in larger series.